Physical fitness, cognition and quality of life in older adults in a central-south zone, Chile (Revista horizonte, 2021)
his research falls within the scope of the active elderly and the importance of the description of physical, cognitive and quality of life parameters. The study was observational, cross-sectional and descriptive. The sample consisted of 337 subjects belonging to groups of senior citizens from the Municipalities of Talcahuano, ConcepcioÌn, Valdivia and Osorno. A digital hand dynamometer was used to measure strength and the test Sit and Reach was used for flexibility. For cognitive impairment the test Mini Mental was performed and the test Unipodal Station was used for static balance. Finally, the test Timed Up and GO was run to measure dynamic balance and the SF-36 questionnaire was responded to study quality of life. The results of the study show that 85.8% of the researched elderly had normal or strong categories regarding strength. Regarding the dynamic balance 94% of those tested were in the altered classification. In relation to the parameter of cognitive impairment only 14.2% were in the normal category and 85.8% had some deficit, besides, 76.3% was within theÂ average, good and excellent category for flexibility. It can be concluded that the strength, flexibility, balance, and cognitive impairment training help slowing or compensating the loss of each of these functions; therefore, they favor the perception of life quality.